Novel STEP-NC Control System - Mohd Azani, Muhammad Faiz (Universiti Teknologi Petronas, 2011)
This project comprised of knowledge derived from software engineering & mechanical engineering utilizing Visual Basic.Net and Standard for Exchange of Product Data Numerical Control (STEP-NC). Visual Basic.Net is a system development tool whereas STEP·NC is a control interface for Computer Numerical Control (CNC) machine tools. The objectives of this project are to develop a system for controlling and managing Computer Numerical Control (CNC) of Standard Electronic of Exchange Product Data Numerical Control (STEPNC), to establish bi-directional data transfer between CNC Controller and the Tum-Mill machine, to establish Extensible Markup Language (XML) & delimiter text file as neutral data file, and to utilize Visual Basic.Net as a tool for application development. There are few problems caused by existing systems such as existing system does not support bi-directional data transfer between Computer Numerical Control (CNC) and the Tum-Mill machines, current system does not provide External Markup Language (XML) as data file for data transfer between Computer Numerical Control (CNC) and the Tum-Mill machine, and existing systems do not generate 'neutral data'. This project used 'Phased-development' as research methodology. After the completion of this project, there are few solid findings are found which are Visual Basic.Net is capable to develop a system for controlling and managing Computer Numerical Control (CNC) of Standard Electronic of Exchange Product Data Numerical Control (STEP-NC), the 'Novel STEP-NC Control System' is capable to support bi-directional data transfer between Computer Numerical Control and Tum-Mill machine, and the 'Novel STEP-NC Control System' is capable to generate XML data file and delimiter text file as 'neutral data'.